[Long John Silver's and Chick-Fil-A in the Avenue campus dining facility] (1994)
Long John Silver's and Chick-Fil-A kiosks at the Avenue dining center in the University Union. Kiosk later became host to a series of different Asian-fusion type eateries. See Page 5 of Mustang News, September 22, 1994 for additional information regarding the addition of Chick-Fil-A and Long John Silver's to Cal Poly Campus Dining.